PENGARUH MOTIVASI MEMBAYAR PAJAK DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Suharti Ningrum; Noor Shodiq Askandar; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine: (1) The Effect of Motivation to Pay Taxes on Individual Taxpayer Compliance, (2) The Effect of Education Level on Individual Taxpayer Compliance, (3) The Effect of Motivation to Pay Taxes and Level of Education on Individual Taxpayer Compliance. Methods of data collection using field research or surveys. The sample used was 30 individual taxpayers. The data analysis technique uses analysis using the SPSS (Statistical Package For Social Science) program. By doing validity and reliability tests. The results showed: (1) Motivation to Pay Taxes has a positive and significant effect on Individual Taxpayer Compliance at the Regional Office of the Directorate General of Taxes Malang in 2020. This is indicated by the regression coefficient value which is positive, namely 0.584 and tcount is greater than ttable (15,137 > 1.654) and the significance value is smaller than the significance value of 5% (0.000 <0.050). These results indicate that the first hypothesis is accepted. (2) The level of education has a positive but insignificant effect on Individual Taxpayer Compliance at the Regional Office of the Directorate General of Taxes Malang in 2020. This is indicated by the regression coefficient that is positive, namely 0.698 and tcount less than ttable (1.120 <1.654) and a significance value that is greater than the 5% significance value (0.265> 0.050). These results indicate that the second hypothesis is accepted. (3) Motivation to Pay Taxes and Education Level have a positive and significant effect on Individual Taxpayer Compliance at the Regional Office of the Directorate General of Taxes Malang in 2020. This is indicated by the positive regression coefficient values, namely 0.582 and 0.273, besides that the Fcount value is greater. than the value of Ftable (114.261> 3.05) and the significance value which is smaller than the significance value of 5% (0.000 <0.050). These results indicate that the third hypothesis is accepted.Keywords: Motivation to Pay Taxes, Level of Education, Individual Taxpayer Compliance